THE REVIEW OF THE ROUTLEDGE COURSE IN KOREAN TRANSLATION BY JIEUN KIAER, 2018. ROUTLEDGE LONDON AND NEW YORK, ISBN 978-1-315-61821-0, PP. 197. - WOJTASIK-DZIEKAN, Emilia (International Journal of Korean Humanities and Social Sciences, 2019)
.